Theatrical inauguration of a parallax view: intertextually - mediated communal memory in Borges’s “Tema del traidor y del héroe” - Mario Bahena Urióstegui (Diálogos, 2015)
This article analyzes the mediation of historical events in “Tema del traidor y del héroe” by Jorge Luis Borges, wherein decisive revolutionary successes are the results of a staged performance—the dramatized execution of independence leader Fergus Kilpatrick. By mixing theater and history, Borges overcomes historical representation in terms of the binaries true/false and real/fiction. This article argues that the historical reality initiated by this performance is the result of an incessant literary mediation. Literature, specifically Festspiele and Shakespearean plays, helped establish a parallax view of the historical events and became the vehicle to validate them as ontological reality. Thus, the historical events, performed or otherwise, are inherently accompanied by literature, having the latter enlighten the former. When Ryan, the main character, discovers the historical theatricality, he also discovers that he cannot change the social significance of the historical events, and himself becomes a part of the historical narrative.